Relationship of the Pregnancy, Stress Biomarkers and Embryonic Losses in Jaffrabadi Buffaloes during Summer Season - Borakhatariya, Devasee N; Singh, Vivek K; Karangiya, Vijay K; Vijyeta, Hardeep P; Vala, Karshan B; Padodara, Ramesh J (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The current study sought to explore the relationship between various pregnancy and stress-related biomarkers, and embryonic mortality in Jaffrabadi buffaloes during summer season. A total of 24 multiparous Jaffarabadi buffaloes were subjected to Ovsynch estrus synchronization and fixed time artificial insemination (FTAI) program, and pregnancy was ascertained by trans-rectal ultrasonography on day 35, and reconfirmed by per rectal palpation on day 60 post-AI. The plasma levels of INF-τ and PGFM were recorded on days 14, 16, 18, and 20 post-AI, whereas the pregnancy specific protein-B (PSPB), heat shock protein 70 (HSP 70), and progesterone were evaluated on days 20, 24, 27, 30, and 40 post-AI. The conception rates obtained were 33.34% (08/24) at 35 days and 16.67% (04/24) at 60 days post-AI, indicating that 50.00% of conceived animals experienced embryonic losses. The overall INF-τ level was significantly (p<0.05) higher in animals with embryonic mortality than in conceived and non-conceived animals. The overall PSPB levels of the conceived animals were significantly higher than that of the non-conceived animals. Moreover, animals with embryonic mortality had PSPB levels significantly higher than those of non-conceived animals and significantly lower than those of conceived animals. The overall PGFM level was significantly (p<0.05) lower in the animals that experienced embryonic death, however, HSP70 concentrations were statistically identical among conceived, non-conceived, and embryonic mortality groups across sampling days. The progesterone levels were significantly higher in animals who conceived and those who had embryonic mortality compared to those not conceived. The plasma levels of all pregnancy and stress biomarkers, with the exception of PSPB, were similar in conceived animals and those that experienced embryonic losses; therefore, poor or retarded embryonic development could be the cause of the embryonic losses that occur in Jaffarabadi buffaloes during the summer.